Core collections for today and tomorrow - Johnson, R.C.; Hodgkin, T.; International Plant Genetic Resources Institute (1999)
Core collections offer a tool to improve access and management of germplasm collections, and therefore are of great interest to those who use and manage plant genetic resources. Over the past few years, experience with core collection has increased as cores for many crops have been developed. The purpose of this publication is to review the current status of core collections and present examples of core development and utilization. The authors were chosen to report on a wide range of views and experiences with core collections, but the examples were not chosen based on desigantion by crop. We find few cores have actually been developed for the major seed crops. Ironically, the use of core collections to improve access to large, unwieldy collections, originally envisioned by Sir Otto Frankel, has not yet come to fruition. Certeinly the complexity and volume of data needed to develop a core collection for large collections can be daunting, but possible approaches and opportunity are described.